2019
DOI: 10.1108/lodj-05-2019-0209
|View full text |Cite
|
Sign up to set email alerts
|

Leader self-efficacy and role ambiguity and follower leader-member exchange

Abstract: Purpose The purpose of this paper is to investigate whether leader self-efficacy and leader role ambiguity are related to follower leader-member exchange (LMX). In addition, the authors examine whether the relationship between follower LMX and turnover intention will be mediated by need satisfaction. Design/methodology/approach Data were collected using an electronic survey tool filled out by 109 leaders and 696 followers. Findings Leader role ambiguity was positively related to an economic LMX relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…One additional suggestion for future research could be further integration of self-determination theory (SDT) (Deci and Ryan, 1985) as an underlying explanatory mechanism. Kuvaas and Buch (2020) findings indicate that economic LMX seems to negatively influence employee outcomes partly by reducing need satisfaction. Therefore, it may be of particular interest, especially considering that social and economic LMX may serve significant, but different roles in need satisfaction, and thereby, in the process of self-determination (Kuvaas and Buch, 2020).…”
Section: Mediators Between Economic Lmx and Follower Outcomesmentioning
confidence: 86%
See 2 more Smart Citations
“…One additional suggestion for future research could be further integration of self-determination theory (SDT) (Deci and Ryan, 1985) as an underlying explanatory mechanism. Kuvaas and Buch (2020) findings indicate that economic LMX seems to negatively influence employee outcomes partly by reducing need satisfaction. Therefore, it may be of particular interest, especially considering that social and economic LMX may serve significant, but different roles in need satisfaction, and thereby, in the process of self-determination (Kuvaas and Buch, 2020).…”
Section: Mediators Between Economic Lmx and Follower Outcomesmentioning
confidence: 86%
“…Limited research exists on different leader characteristics and their influence on followers' perceived LMX relationship. However, Kuvaas and Buch (2020) found that leader role ambiguity was positively related to follower economic LMX and negatively related to follower social LMX. Since role ambiguity is often experienced as a type of strain, these leaders may simply not have the necessary resources to build social LMX relationships with their followers (Kopperud et al, 2018).…”
Section: Leader Characteristics and Follower Lmxmentioning
confidence: 89%
See 1 more Smart Citation
“…Accordingly, recent research indicates it is also important to consider psychological need satisfaction as an antecedent of positive leadership styles, as to better understand why leaders engage into behaviors conductive of such styles ( Paas et al, 2020 ). Second, prior work has mostly adopted a single level approach to psychological need satisfaction, overlooking how psychological need satisfaction is embedded in complex relations between leaders and followers ( Kuvaas and Buch, 2019 ; Xie et al, 2020 ) that cross multiple levels of analysis ( Schreurs et al, 2014 ; Batistič et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…LMX refers to the fact that leaders develop differentiated relationships with their employees ( Graen and Uhl-Bien, 1995 ), where high-quality relationships are characterized by exchanges based on mutual trust, respect, liking, and influence ( Liden and Maslyn, 1998 ) and lead to positive outcomes for both parties ( Graen and Uhl-Bien, 1995 ; Dulebohn et al, 2012 ; Xie et al, 2020 ). Since LMX is considered as need-driven ( Dulebohn et al, 2012 ) and need-satisfying process ( Kuvaas and Buch, 2019 ) that connects multiple levels of analysis ( Liao et al, 2019 ), we propose that LMX constitutes a mechanism through which leader psychological need satisfaction trickles down to employees, from a dyadic viewpoint.…”
Section: Introductionmentioning
confidence: 99%